Études Des Caractéristiques Et Des Déterminants Des Mariages Consanguins Dans La Ville De Tiflet (Maroc) - Zhour, Abbad; Ahmed, Drissi; Soulaymani, Abdelmajid; Abderrazak, Khadmaoui; Abdallah, Oukarroum (European Scientific Journal, ESJ, 2016)
The practice of consanguineous marriage is still very widespread in Morocco and in the Arab-Muslim world, where the customs as well as the cultural, economic and social motivations have most often an influence on the marital choice within the family. The purpose of this study is to define the determinants of this practice in the city of Tiflet and regions (Morocco). A survey was conducted on 1000 pairs randomly sampled between June and November of 2012. The results reveal a high level of consanguinity (38.9 %) and a significant association between this marital practice and the geographical and sociocultural factors such as: the place of residence before marriage, the education level, the profession and the age in the marriage.